DINAMIKA HUBUNGAN KETERASINGAN DENGAN TRANSMISI MEMORI DALAM NOVELLA “TEMPÊTE” KARYA J. M. G. LE CLÉZIO: TELAAH POSTMEMORY - Nadya Annisa Noer; Wening Udasmoro; Subiyantoro Subiyantoro (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2020)
THE DYNAMICS OF RELATIONSHIP BETWEEN ISOLATION AND MEMORY TRANSMISSION IN “TEMPÊTE” NOVELLA BY J. M. G. LE CLÉZIO: A POST-MEMORY REVIEWAbstract: The concept of postmemory, introduced by Hirsch (2012), focuses on the processes through which memories—particularly traumatic memories— of a historical tragedy, “Holocaus”, which is transmitted across generations. Drawing on the elements supporting inter-individual memory transmission, this paper examines the dynamics of human memory within Novel Prize-winning French-Mauritian author J. M. G. Le Clézio's novella entitled “Tempête”. Using a qualitative approach, this study aims to examine the individual forms of memory transmission that are rooted in conditions of isolation, and developed through one trauma site as the memory connector. The presence of semiotics within the story also builds the narration of traumatic memories. It indicates that memory transmission is not necessarily vertical, which is passed from the previous to the next generations. Memory transmission is also not always linear, as there are factors and methods affecting the interpretation of received memory aside from verbally. Thus, the complex relationship between alienation and individual memory transmission processes can directly impact individuals' life projection.Keywords: French Literature, Memory Transmission, Postmemory, TraumaDINAMIKA HUBUNGAN KETERASINGAN DENGAN TRANSMISI MEMORI DALAM NOVELLA “TEMPÊTE” KARYA J. M. G. LE CLÉZIO: TELAAH POSTMEMORY Abstrak: Postmemory sebagai konsep digagas oleh Hirsch (2012), berfokus pada proses transmisi memori. Khususnya memori traumatis dari peristiwa historis “Holokaus” yang diwarisi generasi penerus, disebut juga antargenerasi. Berangkat dari elemen-elemen pendukung pewarisan memori melalui satu individu pada individu lainnya, tulisan ini menelaah kedinamisan konsep memori manusia di dalam novella yang berjudul “Tempête” karya peraih hadiah Nobel franco-mauritian, J. M. G. Le Clézio. Menggunakan pendekatan kualitatif, penelitian ini bertujuan untuk mengkaji bentuk-bentuk transmisi memori individual yang berkembang dari kondisi keterasingan di dalam satu lokasi sebagai penghubung memori. Unsur simbolisme dan semiotik turut membingkai narasi sebagai indikasi memori traumatis di dalam karya. Hasil penelitian ini menunjukkan bahwa transmisi memori tidak selalu bersifat vertikal, yaitu yang diturunkan dari generasi sebelum terhadap generasi seterusnya. Transmisi memori juga tidak selalu bersifat linear, karena adanya faktor dan cara yang memengaruhi interpretasi memori selain daripada lisan. Kompleksitas hubungan keterasingan dan proses transmisi memori individu dapat berdampak langsung pada proyeksi kehidupan seseorang.Kata Kunci: Sastra Prancis, Transmisi Memori, Postmemory, Trauma Permalink/DOI: dx.doi.org/10.17977/um015v48i22020p155